PENGARUH MODAL KERJA DAN PENGALAMAN KERJA TERHADAP PRODUKSI DAN PENDAPATAN PENGUSAHA BATIK DI KOTA DENPASAR - Indri Ani, Ni Wayan Ika Asri; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The Province of Bali is one of the islands that has a small creative industrial sector that continues to grow to this day, for example the works of art include dance, music, carving, painting, and handicrafts. One industry that has the potential to be developed is batik. This study aims to analyze working capital and work experience on the production and income of batik entrepreneurs in Denpasar City. D ata used are primary data by distributing questionnaires to batik entrepreneurs in the city of Denpasar. The population used were all batik entrepreneurs in Denpasar City. The samples used were as many as 57 batik entrepreneurs in the city of Denpasar, using Probability Sampling technique, using the Proportionate Random Sampling method. The analysis technique used in this study is path analysis. The results show that working capital and work experience have a positive and significant effect on the production of batik entrepreneurs in the city of Denpasar. Working capital, work experience and production have a positive and significant effect on the income of batik entrepreneurs in Denpasar City. Production significantly mediates the effect of working capital and work experience on the income of batik entrepreneurs in Denpasar City.